1985
DOI: 10.1021/bi00343a006
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-transform infrared difference spectroscopy of rhodopsin and its photoproducts at low temperature

Abstract: Fourier-transform infrared difference spectroscopy has been used to detect the vibrational modes in the chromophore and protein that change in position or intensity between rhodopsin and the photoproducts formed at low temperature (70 K), bathorhodopsin and isorhodopsin. A method has been developed to obtain infrared difference spectra between rhodopsin and bathorhodopsin, bathorhodopsin and isorhodopsin, and rhodopsin and isorhodopsin. To aid in the identification of the vibrational modes, we performed experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
121
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(146 citation statements)
references
References 53 publications
(72 reference statements)
25
121
0
Order By: Relevance
“…So did the v(C=N+) band between Rh, B, and isorhodopsin. Most significantly, however, the three Ndeuterated samples gave three different v(C=N+) frequencies (167). They are 1624 for B, 1631 for isorhodopsin, and 1624 cm-for Rh (164,200) in agreement with previous results of Siebert et al (164,200).…”
Section: Protonation and Hydrogen Bondingsupporting
confidence: 91%
See 1 more Smart Citation
“…So did the v(C=N+) band between Rh, B, and isorhodopsin. Most significantly, however, the three Ndeuterated samples gave three different v(C=N+) frequencies (167). They are 1624 for B, 1631 for isorhodopsin, and 1624 cm-for Rh (164,200) in agreement with previous results of Siebert et al (164,200).…”
Section: Protonation and Hydrogen Bondingsupporting
confidence: 91%
“…Now, since this is so, the uniform v(C=Nf ) might not correspond to the same potential, average proton position and charge distribution in the proton bridge. This is clearly illustrated by the recent differential infrared experiments of Bagley et al (167). These researchers performed experiments on hydrated and deuterated films of native rod outer segment (ROS) and ROS regenerated with retinals with isotopic substitution at C-15.…”
Section: Protonation and Hydrogen Bondingmentioning
confidence: 96%
“…Such bands are absent from the low-temperature spectra of myoglobin (Alben & Caughey, 1968), cytochrome oxidase (Fiamingo et al, 1981), rhodopsin (Bagley et al, 1985(Bagley et al, , 1989, and bacteriorhodopsin (Bagley et al, 1982). Such bands are also absent from the infrared spectra of another Ni,Fe enzyme, CO dehydrogenase (Kumar & Ragsdale, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…They emphasized the potential of IR-difference spectroscopy to study protein conformational changes. Along with our initial work in 1981, Laura Eisenstein at the University of Illinois used FTIR difference spectroscopy starting in 1982 to study BR [16,17] and later rhodopsin [18,19]. In the case of BR, this work confirmed that the SB in the BR 570 and the K 630 intermediate are both protonated.…”
Section: Addition Studiesmentioning
confidence: 86%
“…In one experiment reported in 1981, lysines in BR were substituted with lysines where the ε-amino group was either completely or partial labeled with 15 N [6]. The results disproved the previously suggested [140] hypothesis [18] that two different lysine residues interacted with the retinylidene Schiff base (SB). In a second experiment ε-amino N 15 lysine labeling was combined with proteolytic fragmentation and recombination of intact BR from these fragments [194].…”
Section: Stable Isotope Labeling Of Membrane Proteinsmentioning
confidence: 97%